Pancasila sebagai Perjanjian Luhur Memperkuat Nilai-Nilai Kemanusiaan Indonesia di Era Teknologi - Walukow, Devy Stany; Pesik, Tobian Habel (Proceedings of The National Conference on Indonesian Philosophy and Theology, 2025)
Pancasila is the strength, lifeblood, and future of the Indonesian state. Established on 1 June 1945 as the foundation of the state, Pancasila is an ideological foundation derived from cultural values and mutual agreement. Ratified on 18 August 1945, Pancasila became the constitutional foundation of the state through a lengthy process marked by differences of opinion but ultimately reached a compromise. Therefore, Pancasila as the foundation of the state strengthens Indonesia's existence and diversity within the concept of a united and sovereign nation. However, what is happening today is the proliferation of disputes over differences and diversity on social media. Pancasila, as an ideological foundation, has not been well understood, while Pancasila as a constitutional foundation is understood but still violated. Pancasila, which was agreed upon on 1 June 1945 and as a result of a compromise on 18 August 1945, still needs to be continuously socialized through education. This is very important to prevent conflicts related to differences and diversity in society. Pancasila as an ideological foundation must strengthen its position as a consensus of conscience among every group and class in society. This understanding can strengthen the Pancasila of 18 August 1945. Although it is a compromise, Pancasila still upholds human values as universal values accepted by all Indonesian society. Thus, the values of Pancasila reinforce the power of the ‘heart’ and public awareness as a noble agreement that can suppress and prevent the erosion of social bonds. Pancasila can influence the formation of opinions about human values in the technological era. This study was analyzed using a qualitative-descriptive approach, using books, journals, and newspapers as theoretical references and empirical data from the field.AbstrakPancasila adalah kekuatan, napas kehidupan, dan masa depan negara Indonesia. Pancasila yang ditetapkan pada 1 Juni 1945 sebagai landasan negara merupakan landasan ideologis yang berasal dari nilai-nilai budaya dan hasil kesepakatan bersama. Pancasila yang disahkan pada 18 Agustus 1945 merupakan landasan konstitusional negara melalui proses panjang akibat perbedaan pandangan namun akhirnya mencapai kompromi. Oleh karena itu, Pancasila sebagai landasan negara memperkuat keberadaan dan keragaman Indonesia dalam konsep bangsa yang bersatu dan berdaulat. Namun, yang terjadi saat ini adalah maraknya perselisihan mengenai perbedaan dan keragaman di media sosial. Pancasila sebagai landasan ideologis belum dipahami dengan baik, sementara Pancasila sebagai landasan konstitusional dipahami tetapi masih dilanggar. Pancasila yang disepakati pada 1 Juni 1945 dan sebagai hasil kompromi pada 18 Agustus 1945, masih perlu terus disosialisasikan melalui pendidikan. Hal ini sangat penting untuk mencegah konflik terkait perbedaan dan keragaman di masyarakat. Pancasila sebagai landasan idiil harus memperkuat posisinya sebagai kesepakatan hati nurani setiap kelompok dan golongan dalam masyarakat. Pemahaman ini dapat memperkuat Pancasila 18 Agustus 1945. Meskipun merupakan kompromi, Pancasila tetap menjunjung nilai-nilai kemanusiaan sebagai nilai-nilai universal yang diterima oleh seluruh masyarakat Indonesia. Dengan demikian nilai-nilai Pancasila mempertegas kekuatan dari “hati” dan kesadaran masyarakat sebagai perjanjian luhur yang dapat menekan dan mencegah tergerusnya ikatan sosial. Pancasila dapat mempengaruhi pembentukan opini tentang nilai-nilai manusia di era teknologi. Studi ini dianalisis menggunakan pendekatan kualitatif-deskriptif, dengan menggunakan buku, jurnal, dan koran sebagai referensi teoretis dan data empiris dari lapangan.